2007
DOI: 10.5465/amle.2007.24401700
|View full text |Cite
|
Sign up to set email alerts
|

Even if the Tower Is “Ivory,” It Isn't “White:” Understanding the Consequences of Faculty Cynicism.

Abstract: Prompted by a seemingly growing level of cynicism within academia, on the part of Academy of Management members in particular, I developed a new measure of cynicism and investigated a previously untested structural model in which cynicism is related in sequence to organizational identification, affective commitment, job satisfaction, and turnover intentions. Data were obtained from 379 faculty members who were participants in the 2004 Academy of Management Meeting. Structural equation modeling was used to repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
15

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(66 citation statements)
references
References 77 publications
0
51
0
15
Order By: Relevance
“…This is because cynicism is expressed destructively (e.g., uncooperative) and actively (e.g., employing voice but in a disparaging way) (Wilkerson et al, 2008). Empirical evidence showed that employee cynicism associates negatively with organizational commitment (Andersson & Bateman, 1997), organizational citizenship behaviour (Abraham, 2000;Bedeian, 2007), job satisfaction (Abraham, 2000), and positively with grievance (Wanous, Reichers, & Austin, 2000), badmouthing (Wilkerson et al, 2008), and employee turnover (Bedeian, 2007). Therefore, it is highly relevant to investigate its role in employee-customer service encounters (Ashforth & Humphrey, 1993;Dormann & Zapf, 2004).…”
Section: Service Context and Employee (Re)actionsmentioning
confidence: 99%
“…This is because cynicism is expressed destructively (e.g., uncooperative) and actively (e.g., employing voice but in a disparaging way) (Wilkerson et al, 2008). Empirical evidence showed that employee cynicism associates negatively with organizational commitment (Andersson & Bateman, 1997), organizational citizenship behaviour (Abraham, 2000;Bedeian, 2007), job satisfaction (Abraham, 2000), and positively with grievance (Wanous, Reichers, & Austin, 2000), badmouthing (Wilkerson et al, 2008), and employee turnover (Bedeian, 2007). Therefore, it is highly relevant to investigate its role in employee-customer service encounters (Ashforth & Humphrey, 1993;Dormann & Zapf, 2004).…”
Section: Service Context and Employee (Re)actionsmentioning
confidence: 99%
“…Employees high on organizational cynicism typically are emotionally detached and alienated from their work environment, and they often hold negative, malevolent, hostile, and overly critical attitudes towards co-workers, emphasizing their own alleged moral superiority (Abraham, 2000). Cynicism has been shown to diminish individuals' job satisfaction (Johnson & O'Leary-Kelly, 2003), organizational commitment and identification (Bedeian, 2007;Treadway et al, 2004), and extra-role behaviors (Andersson & Bateman, 1997).…”
Section: Individuals' and Subgroups' Organizational Cynicismmentioning
confidence: 99%
“…Bedeian (2007) indicated that OI is an antecedent of OC. Meyer et al (2006) further suggested that OC mediates the effects of OI on employee behavioral intention and outcome.…”
Section: H13: Js Positively Affects Ocmentioning
confidence: 99%